1995
DOI: 10.1006/aphy.1995.1083
|View full text |Cite
|
Sign up to set email alerts
|

Potential Scattering on R3 ⊗ S1

Abstract: In this paper we consider non-relativistic quantum mechanics on a space with an additional internal compact dimension, i.e. R 3 ⊗S 1 instead of R 3 . More specifically we study potential scattering for this case and the analyticity properties of the forward scattering amplitude, T nn (K), where K 2 is the total energy and the integer n denotes the internal excitation of the incoming particle. The surprising result is that the analyticity properties which are true in R 3 do not hold in R 3 ⊗ S 1 . For example, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(55 citation statements)
references
References 2 publications
4
51
0
Order By: Relevance
“…the S 1 compactification. We were motivated to undertake this work from work of Khuri [27] who considered potential scattering with a compact spatial coordinate. He showed the lack of analyticity of the forward scattering amplitude under certain circumstances.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…the S 1 compactification. We were motivated to undertake this work from work of Khuri [27] who considered potential scattering with a compact spatial coordinate. He showed the lack of analyticity of the forward scattering amplitude under certain circumstances.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Khuri [27] identifies a conservation rule: K 2 = k 2 + (n 2 /R 2 ) = k ′2 + (m 2 /R 2 ). Moreover, it is argued that the scattered wave has only (2[KR] + 1) components and those states with (m 2 /(R 2 ) > k 2 + (n 2 /R 2 ) are exponentially damped for large |x| and consequently, these do not appear in the scattered wave.…”
Section: Scattering In Nonrelativistic Quantum Mechanics With a Compamentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it will be quite interesting to study analyticity properties of scattering amplitude in a higher dimensional theory where some of the spatial coordinates are compactified. It was pointed out, in the context of potential scattering [56,57], that for nonrelativistic theory, the analyticity properties of scattering amplitudes are different from those of a nonrelativistic theory which has no compactified spatial coordinates. It is to be noted that momenta associated with compact directions are discrete.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…[49]. He showed that analytical properties of the forward scattering amplitude T nn (s, t = 0), which are true in Ê 3 , do not necessarily hold in Ê 3 ⊗ S 1 for n > 0.…”
Section: B Uhe Neutrino and Weak-scale String Theoriesmentioning
confidence: 99%